The Effect of the Type and Composition of the Adhesive on the Physical Properties and the Rate of Combustion Hyacinth Biobriquettes - Lalu Muhamad Alfian Ramdani; Sukainil Ahzan; Dwi Sabda Budi Prasetya (Lensa: Jurnal Kependidikan Fisika, 2020)
This study aimed to identify the effects of variety and composition of the adhesive used to the physical properties and the rate of combustion hyacinth biobriquettes. The physical properties referred to are water content, density and heating value. This research is an experimental study with a literacy study conducted in 3 stages, preparing tools and materials, making biobriquettes, and testing biobriquettes. The main ingredients used in the manufacture of biobriquettes are water hyacinth which is obtained at the Batujai Dam, Central Lombok Regency and the adhesive materials used are wheat flour, tapioca flour and cement. The method used to test the water content and density of the biobriquette was oven, while the calorific value and the rate of combustion were by heating water from the biobriquette combustion. The results showed that the biobriquette water content ranged from 5.138% - 13.953%, density 0.412 g/cm3 - 0.513 g/cm3, calorific value 2984.520 cal - 4476.780 cal, and combustion rate 0.029543 g/s - 0.042431 g/s. Based on the test results, it is known that the addition of adhesive material causes the water content, density, and combustion rate of the biobriquette to increase but the calorific value tends to decrease.